2002
DOI: 10.1021/bi026096m
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Is Required for the Catalytic Activity of the Human Deubiquitinating Isopeptidase T

Abstract: Two recombinant human isopeptidase T isoforms, ISOT-S and ISOT-L, differing by an insertion of 23 amino acids in ISOT-L, were previously classified as thiol proteases. Both contain one Zn2+-binding site of high-affinity, which is part of a cryptic nitrilo-triacetate-resistant pocket (site 1). A second Zn2+ site (site 2) was disclosed when both isoforms of the holoenzyme were incubated with an excess of Zn2+. The firmly bound Zn2+ of site 1 could be removed either slowly by dialysis against 1,10-phenanthroline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The exact mechanism by which (PyDT) 2 Zn increases the proteasomal chymotrypsin-like activity within the cell is not understood and needs to be further investigated. It has also been reported that human deubiquitinating isopeptidase T has three sets of zinc-binding sites and that zinc binding to high affinity sites is required for its activity (Gabriel et al, 2002). However, by binding to the set of low affinity sites, zinc ions completely abolish isopeptidase T enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism by which (PyDT) 2 Zn increases the proteasomal chymotrypsin-like activity within the cell is not understood and needs to be further investigated. It has also been reported that human deubiquitinating isopeptidase T has three sets of zinc-binding sites and that zinc binding to high affinity sites is required for its activity (Gabriel et al, 2002). However, by binding to the set of low affinity sites, zinc ions completely abolish isopeptidase T enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Since zinc is required for the catalytic activity of the human deubiquitinating isopeptidase T (Gabriel et al, 2002), it is possible that isopeptidase activity located on 19S regulatory subunit of the 26S proteasome could also be activated by (PyDT) 2 Zn or zinc ions released from the complex during the possible intracellular degradation. The fact that the high level of ubiquitinated proteins still remained until the end of treatment could be explained by the proteasomal inhibition observed again at the end of the treatment and by the formation of aggresomes.…”
Section: Discussionmentioning
confidence: 99%
“…The tandem UBA domains associate with the distal Ub units when USP5 catalyzes the hydrolysis of polyUb chains [18]. ZnF is the activation domain of USP5 that is recognized by the C-terminal extension of Ub [19], [20]. The catalytic domain consists of the C-box and H-box lobes including substrate binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…IsoT-3 is encoded by a different gene, USP13, and shares 54.8% identity with IsoT-S (31). Whereas most in vitro studies aimed at understanding the substrate specificity of IsoT have been conducted using human IsoT, very little is known about the substrate specificity of the other two human isoforms (28,(33)(34)(35)(36). IsoT disassembles at least four types of polyubiquitin isoforms: K48-, K63-, K29/K6-linked, and linear chains (26,28).…”
mentioning
confidence: 99%